2023
DOI: 10.1002/wcs.1668
|View full text |Cite
|
Sign up to set email alerts
|

Revealing visual working memory operations with pupillometry: Encoding, maintenance, and prioritization

Damian Koevoet,
Christoph Strauch,
Stefan Van der Stigchel
et al.

Abstract: Pupillary dynamics reflect effects of distinct and important operations of visual working memory: encoding, maintenance, and prioritization. Here, we review how pupil size predicts memory performance and how it provides novel insights into the mechanisms of each operation. Visual information must first be encoded into working memory with sufficient precision. The depth of this encoding process couples to arousal‐linked baseline pupil size as well as a pupil constriction response before and after stimulus onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 132 publications
0
0
0
Order By: Relevance
“…Interestingly, research on the pupillary light response found it to be modulated by covert attention and visuospatial working memory (Binda & Murray, 2015;Hustá et al, 2019;Mathôt & van der Stigchel, 2015;Zokaei et al, 2019), again highlighting the profound connection between attention and eye behavior. The pupil diameter was shown to reflect phases of encoding, maintenance, and prioritization within the visuospatial working memory (Koevoet et al, 2023). This suggests that even the pupillary response is indicative of attentional shifts, whether directed towards external stimuli or internal representations.…”
Section: Internal Coupling As a Marker Of Internal Attention Shiftsmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, research on the pupillary light response found it to be modulated by covert attention and visuospatial working memory (Binda & Murray, 2015;Hustá et al, 2019;Mathôt & van der Stigchel, 2015;Zokaei et al, 2019), again highlighting the profound connection between attention and eye behavior. The pupil diameter was shown to reflect phases of encoding, maintenance, and prioritization within the visuospatial working memory (Koevoet et al, 2023). This suggests that even the pupillary response is indicative of attentional shifts, whether directed towards external stimuli or internal representations.…”
Section: Internal Coupling As a Marker Of Internal Attention Shiftsmentioning
confidence: 94%
“…However, pupil size is not a mere reflexive adaptation to the lighting conditions, but increasingly recognized as a read-out of different mental activities. Several lines of research have advocated for the use of pupillometry as a non-invasive tool for measuring cognitive processes, including attention, memory, and visual imagery (for reviews see Koevoet et al, 2023;Mathôt, 2020;Strauch et al, 2022). For example, pupil diameter (PD) is affected by cognitive workload, with increased workload resulting in increased PD, which is an established objective measure of workload demand (for reviews see Beatty & Lucero-Wagoner, 2000;van der Wel & van Steenbergen, 2018 Moreover, visual attention may even interfere with the PLR.…”
Section: Imagery Of Brightnessmentioning
confidence: 99%
“…Light induces a discharge of noradrenaline in the LC which increases its activity, leading to a change in pupillary response. Moreover, the differences between the different illumination conditions could correspond to fluctuations in arousal, reflecting the tonic discharge of the locus coeruleus (37). Indeed, bottom-up processing can lead to variations in LC discharge, which acts as a feature-based filter and allows a salient stimulus to enter visual working memory when presented (38).…”
Section: -Bottom-up Influencementioning
confidence: 99%
“…In this study, we were able to observe top-down and bottom-up modulations on the pupil over long periods of time. However, it would be interesting to be able to characterise attentional processing using shorter pupil signals (37). This would allow us to study more dynamic aspects of attention orientation and regulation, and thus gain a better understanding of the physiological mechanisms involved in attention modulation of the pupil at rest and during a task.…”
Section: -The Pupil An Integrated Indexmentioning
confidence: 99%